Planned Complex Suicide: A Conundrum to Unravel (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
The definition of complex suicide as the use of more than one method to induce death has been widely accepted in the forensic literature. This article presents two cases of complex suicide. The first was a 33-year-old male who had consumed organo phosphorus poison before hanging himself with a cloth. In the second case, a 20-year-old male had consumed kerosene and then hanged himself with a plastic rope. The specific circumstances of the case are described and relevant literature is briefly reviewed. The investigation of scene, the method employed, the autopsy findings and the interview with their relatives altogether pointed towards a suicidal aetiology. Knowledge of varied and sometimes unusual suicide methods is important to the forensic investigator to prevent unnecessary criminal investigation and to reliably and confidently establish manner and cause of death.
Keywords: Complex suicide; Poison, Hanging; Autopsy; Ligature mark; Criminal investigation; Death Forensic science laboratory